Calcium alginate gel for internal curing of cementitious materials and use thereof
Patent Information
- Application Number
- CN202611204451.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-10
- Publication Date
- 2026-10-09
AI Technical Summary
[0005]本发明的目的是提供一种用于水泥基材料内养护的海藻酸钙凝胶,以解决传统内养护材料溶胀性能不稳定、粒径难以精准控制、对力学性能负面影响大的问题
[0037]本发明的海藻酸钙凝胶,具有可控的粒径范围和稳定的三维网络结构,能够通过粒径的阶梯式分布匹配不同水泥基材料的孔隙特征;应用于水泥基材料内养护时,掺量为水泥质量的0.1%-2%,该凝胶在水泥基材料中形成微米级(0.01~13μm)的高水灰比区域,主要在1~3天龄期内释放水分,精准匹配水泥水化需水规律,可有效释放内养护水促进水泥水化;同时,相较于传统超吸水聚合物,该凝胶显著降低对水泥基材料力学性能的负面影响,提高混凝土耐久性。
Smart Images

Figure CN122878472A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of civil engineering materials technology, specifically relating to a calcium alginate gel for internal curing of cement-based materials and its application. Background Technology
[0002] Concrete, as the most widely used building material in modern civil engineering, directly affects the safe service life of engineering structures due to its durability. With the widespread application of high-performance concrete and ultra-high-performance concrete, a low water-cement ratio (usually less than 0.40) has become a key means to achieve high strength and high density in concrete. However, in the early stages of hydration, low water-cement ratio concrete experiences rapid consumption of internal free water, making it difficult for external curing water to penetrate. This leads to a sharp drop in internal relative humidity, resulting in significant self-shrinkage and subsequently early cracking. This self-shrinkage cracking not only damages the density and integrity of the concrete but also exposes it to corrosive ions (such as Cl-). - SO4 2- The intrusion of [something] provides a channel, accelerating concrete deterioration or steel corrosion, and severely shortening the service life of the structure.
[0003] Internal curing technology, by introducing water-retaining materials into the concrete to pre-absorb and store moisture, gradually releases it during hydration, providing an internal water source for continuous cement hydration. This is an effective way to solve the autogenous shrinkage cracking problem in low water-cement ratio concrete. Superabsorbent polymers (SAPs) are currently the most widely used internal curing materials. They can absorb tens or even hundreds of times their own weight in water, absorbing water during the concrete mixing stage and releasing it after hardening for internal curing. However, SAPs have a significant drawback in internal curing applications: they are less effective in high-calcium cement pastes. 2+ The swelling rate in the environment is limited and unstable, making it difficult to accurately control the timing and amount of internal curing water release. More importantly, SAP absorbs a large amount of water during the mixing process, forming large pore defects after hardening, which significantly reduces the mechanical properties of concrete and restricts its application in high-performance concrete.
[0004] Chinese patent CN117645425B discloses a concrete rust-inhibiting internal curing agent and its preparation method. This internal curing agent employs a hybrid core-shell structure, using a step-by-step preparation process to load a healing component onto a loading component. Then, a superabsorbent resin is used to encapsulate and fill the inorganic rust-inhibiting component, ultimately forming an internal curing agent with self-curing, self-healing, and rust-inhibiting functions. However, this preparation method requires complex processes such as ultrasonic homogenization, multi-temperature stirring at 30-65℃, and protective gas atmosphere protection. The process conditions are harsh, and the formation of the core-shell structure depends on the step-by-step assembly and encapsulation of multiple components. The particle size control process is complex and has limited repeatability, restricting its large-scale application in cement-based materials. Summary of the Invention
[0005] The purpose of this invention is to provide a calcium alginate gel for internal curing of cement-based materials, so as to solve the problems of unstable swelling performance, difficulty in precise control of particle size, and large negative impact on mechanical properties of traditional internal curing materials.
[0006] A second objective of this invention is to provide an application of the above-mentioned calcium alginate gel as an internal curing agent in cement-based materials.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0008] A calcium alginate gel for internal curing of cement-based materials is prepared by a method comprising the following steps:
[0009] 1) Under stirring, sodium alginate powder is added to hydrochloric acid with a pH value ≤ 0.01 to obtain an acidified system;
[0010] 2) Add calcium chloride powder to the acidification system and add water to obtain a mixture;
[0011] 3) Adjust the pH of the mixture to 6.5-7.5, react for 18-30 hours, and obtain the reaction product;
[0012] 4) Wash the reaction product and dry it to constant weight to obtain the final product.
[0013] The calcium alginate gel of the present invention achieves a precise correspondence between the gel size and the raw material size through the protonation theory, providing a solution for the internal curing of cement-based materials with precise and controllable particle size, simple preparation process, and minimal impact on mechanical properties.
[0014] Furthermore, the container is prepared by first wetting it with hydrochloric acid with a pH value ≤ 0.01, and then hydrochloric acid with a pH value ≤ 0.01 is added to the container.
[0015] Preferably, the hydrochloric acid has a pH value of 0-0.01. More preferably, the hydrochloric acid has a pH value of 0.005-0.01.
[0016] In step 1), add 30-80 mL of hydrochloric acid to every 30-70 g of sodium alginate powder.
[0017] The acidification system in step 1) causes the sodium alginate powder to be protonated and precipitated.
[0018] In step 1), the molar ratio of mannuronic acid and guluronic acid in the sodium alginate powder is 1.5-2.0:1.
[0019] Preferably, in step 1), the molar ratio of mannuronic acid and guluronic acid in the sodium alginate powder is 1.5:1 or 2.0:1.
[0020] In step 1), the particle size of the sodium alginate powder is <200μm.
[0021] Furthermore, the sodium alginate used meets the following requirements: the viscosity of a 10% sodium alginate solution at 20°C is 100-300 mPa·s.
[0022] In step 2), the amount of calcium chloride powder added satisfies the mass ratio of calcium chloride powder to sodium alginate of 20-100:50; the amount of water added satisfies the concentration of calcium chloride in the resulting mixture of 0.1-1.0 mol / L.
[0023] The reaction in step 2) causes the precipitated sodium alginate to exchange and chelate with calcium ions.
[0024] In step 3), sodium hydroxide is used to adjust the pH of the mixture.
[0025] Preferably, in step 3), the pH of the mixture is adjusted to neutral.
[0026] Furthermore, in step 4), the reaction product is washed with deionized water at least three times to remove excess ions.
[0027] In step 4), the drying temperature is 30-50℃.
[0028] The calcium alginate gel of the present invention for internal curing of cement-based materials is prepared based on the protonation theory using sodium alginate as raw material. It has the characteristics of precise and controllable particle size, stable swelling performance, and minimal impact on mechanical properties.
[0029] The calcium alginate gel obtained by this invention has a three-dimensional network structure composed of calcium alginate, wherein the three-dimensional network structure contains chelated calcium ions. The particle size of the calcium alginate gel obtained by this invention is 2-180 μm.
[0030] The application of the above-mentioned calcium alginate gel as an internal curing agent in cement-based materials.
[0031] The calcium alginate gel is incorporated into the cement-based material at a mass ratio of 0.1% to 2% of the cement mass.
[0032] Furthermore, the particle size of calcium alginate gel used as an internal curing agent in cement-based materials is 2-180 μm.
[0033] The water-cement ratio of the cement-based material is 0.30-0.50.
[0034] Furthermore, the calcium alginate gel is incorporated into the cementitious material at a mass ratio of 0.1% to 2% of the cementitious material mass.
[0035] The calcium alginate gel of this invention is prepared by protonating sodium alginate powder in hydrochloric acid with a pH ≤ 0.01 to precipitate sodium alginate particles; adding calcium chloride powder and stirring until homogeneous, while simultaneously adding water to adjust the total volume of the solution; adjusting the pH of the system to neutral, allowing the precipitated sodium alginate to exchange and chelate with calcium ions; and finally washing and drying to obtain the final product. This invention achieves precise control of gel particle size by adjusting the size of the sodium alginate powder and stable control of swelling performance by adjusting the concentration of the calcium chloride solution.
[0036] Testing revealed that the calcium alginate gel of this invention exhibits a volume swelling ratio of 5 to 50 times its dry volume under saturated water absorption; an equilibrium swelling degree of 30 to 80% in deionized water; and a pore size distribution of 0.1 to 10 μm.
[0037] The calcium alginate gel of this invention has a controllable particle size range and a stable three-dimensional network structure, which can match the pore characteristics of different cement-based materials through the stepped distribution of particle size. When applied to the internal curing of cement-based materials, the dosage is 0.1%-2% of the cement mass. The gel forms a high water-cement ratio region in the cement-based material at the micron level (0.01-13μm), and mainly releases water within 1-3 days of curing, precisely matching the water demand of cement hydration. It can effectively release internal curing water to promote cement hydration. At the same time, compared with traditional superabsorbent polymers, this gel significantly reduces the negative impact on the mechanical properties of cement-based materials and improves the durability of concrete. Attached Figure Description
[0038] Figure 1 The molecular structure diagram of calcium alginate obtained in this invention is shown.
[0039] Figure 2 SEM images of the area surrounding calcium alginate in the cement paste sample of Example 1 are shown below; where a) is an SEM image and b) is a binary image, CA pore represents calcium alginate pores, interface area represents the interface region, and Cement matrix represents the cement matrix.
[0040] Figure 3 This is an extraction diagram of unhydrated cement in the area surrounding calcium alginate gel in the cement paste sample of Example 1;
[0041] Figure 4 The image shows the morphology of the calcium alginate surface hydration products in the cement paste sample of Example 1; where CA represents calcium alginate.
[0042] Figure 5 A fitting graph of predicted and experimental data for the compressive strength of cement-based materials with added calcium alginate gel;
[0043] Figure 6 This is a schematic diagram showing the impermeability recovery rate of Examples 1-2 and the comparative example. Detailed Implementation
[0044] The present invention will be further described below with reference to specific embodiments.
[0045] In this specific embodiment, the sodium alginate used meets the requirement that a 10% sodium alginate solution has a viscosity of 150-250 mPa·s at 20°C. The calcium chloride used is of analytical grade.
[0046] Example 1
[0047] The calcium alginate gel used for internal curing of cement-based materials in this embodiment is prepared by a method including the following steps:
[0048] 1) Wet the beaker with hydrochloric acid with a pH of 0.01, and add 50 ml of hydrochloric acid with a pH of 0.01 to the beaker;
[0049] Using a magnetic stirrer, slowly add 50g of sodium alginate powder (the ratio of mannuronic acid to guluronic acid is about 1.5:1, the particle size is 10~50μm, and the average particle size is 40μm) to hydrochloric acid while stirring to obtain an acidification system, so that the sodium alginate powder is protonated and precipitated.
[0050] 2) Add calcium chloride powder to the acidification system and stir evenly. At the same time, add deionized water to make the total volume of the mixture reach 2.25L. Control the concentration of CaCl2 in the mixture to be 0.4mol / L.
[0051] 3) Adjust the pH of the mixture to 7.0 using sodium hydroxide, react for 24 hours, and obtain the reaction product;
[0052] 4) Wash the reaction product three times with deionized water, filter it, and dry it in a 40°C drying oven until constant weight to obtain calcium alginate gel.
[0053] The structural characteristics of the calcium alginate gel obtained in this embodiment are as follows: Figure 1 As shown, the gel is a three-dimensional network structure composed of calcium alginate, and the three-dimensional network structure contains chelated calcium ions. The particle size of the gel is 40 μm (average particle size).
[0054] In this embodiment, calcium alginate gel was added to a cement-based material with a water-cement ratio of 0.35 at a mass ratio of 1% of the cement, and the mixture was cured for 28 days to obtain a cement paste sample.
[0055] Example 2
[0056] The calcium alginate gel used for internal curing of cement-based materials in this embodiment is prepared by a method including the following steps:
[0057] 1) Wet the beaker with hydrochloric acid with a pH of 0.01, and add 50 ml of hydrochloric acid with a pH of 0.01 to the beaker;
[0058] Using a magnetic stirrer, slowly add 50g of sodium alginate powder (the ratio of mannuronic acid to guluronic acid is about 1.5:1, the particle size is 10~50μm, and the average particle size is 40μm) to hydrochloric acid while stirring to obtain an acidification system, so that the sodium alginate powder is protonated and precipitated.
[0059] 2) Add calcium chloride powder to the acidification system and stir evenly. At the same time, add deionized water to make the total volume of the mixture reach 2.25L. Control the concentration of CaCl2 in the mixture to be 0.1mol / L.
[0060] 3) Adjust the pH of the mixture to 7.0 using sodium hydroxide, react for 24 hours, and obtain the reaction product;
[0061] 4) Wash the reaction product three times with deionized water, filter it, and dry it in a 40°C drying oven until constant weight to obtain calcium alginate gel.
[0062] The structural characteristics of the calcium alginate gel obtained in this embodiment are as follows: the gel is a three-dimensional network structure composed of calcium alginate, and the three-dimensional network structure contains chelated calcium ions. The particle size of the gel is 40 μm (average particle size).
[0063] In this embodiment, calcium alginate gel was added to a cement-based material with a water-cement ratio of 0.35 at a mass ratio of 2% of the cement, and the mixture was cured for 28 days to obtain a cement paste sample.
[0064] Comparative Example
[0065] The cement paste sample in this comparative example is made of the same cement-based material as in Example 1, without the addition of calcium alginate gel.
[0066] Experimental Example
[0067] This experimental example tests the cement paste samples from Examples 1-2 and the comparative example.
[0068] The test methods are as follows: Volume swelling rate was determined by immersion weighing method, referring to GB / T 1034-2008 "Determination of Water Absorption of Plastics". Equilibrium swelling was determined by equilibrium liquid absorption weighing method, referring to YY / T 1435-2016 "Guideline for Characterization of Hydrogels in Tissue-Engineed Medical Devices". Compressive strength was determined by cube compressive strength test, referring to GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete". Crack self-closing width (impermeability recovery rate) was determined by microscopic imaging method, referring to GB / T 50784-2013 "Technical Standard for On-Site Testing of Concrete Structures".
[0069] Table 1 Performance test results of Examples 1-2 and Comparative Examples
[0070]
[0071] Note: It refers to the volume swelling rate in a saturated water-absorbing state as a multiple of its dry volume.
[0072] The results are as follows Figure 2-6 As shown in Table 1.
[0073] The comparative example is a pure cement paste sample without added calcium alginate gel. Since there is no swelling effect of internal curing gel, its volume swelling rate and equilibrium swelling degree in Table 1 are 0.
[0074] Figure 2 The 2μm in the lower right corner is the length scale. Figure 3 The upper 20-100μm represents the area with a radius of 20-100μm around the calcium alginate (CA) gel in the cement paste sample of Example 1; the lower 13.53%-28.75% represents the content of UHC (unhydrated cement) per unit volume in different areas around CA, which is the content of UHC per unit area in the backscattered image. Figure 4 The micrometers in the lower left corner are all length scales. In the figure, CA represents calcium alginate, and Ca(OH)2 and CSH are calcium hydroxide and calcium silicate hydrate, respectively, which are the hydration products.
[0075] Figure 2-4 SEM, XRD, TG, and FTIR analyses confirmed that the gel is tightly bound to hydration products through Si-O-Ca, Ca-OH, and ionic bonds, promoting the formation of Ca(OH)2 and CSH. The CaCO3 on the gel surface is mainly aragonite, demonstrating a biotemplating effect. Stereoscopic analysis showed that the gel promotes the hydration of large-diameter cement particles, enhancing the degree of hydration.
[0076] from Figure 5 As can be seen from Table 1, the measured compressive strength of Examples 1 and 2 is slightly lower than that of the comparative example; however, the volume swelling rate under saturated water absorption is 18.6 to 31.4 times that of its dry volume; and the equilibrium swelling degree in deionized water is 48.7% to 66.3%, which is far better than that of the comparative example.
[0077] from Figure 6 As shown in Table 1, the permeability recovery rate of the comparative example is less than 40%, while the permeability recovery rate of the example is above 65%, and the permeability recovery rate of Example 2 is around 77%. The results indicate that the permeability recovery rate of the calcium alginate gel of the present invention is significantly improved compared to the undoped group when incorporated in trace amounts.
[0078] In summary, the calcium alginate gel of this invention has precise and controllable particle size, stable swelling performance, and internal curing function, which significantly reduces the negative impact on mechanical properties and provides an effective solution for crack control and durability improvement of low water-cement ratio high-performance concrete.
[0079] The above embodiments are merely illustrative and not restrictive. Any modifications, substitutions, or reorganizations of the technical solutions of this invention without departing from the spirit or basic characteristics of this invention should be covered within the protection scope of this invention.
Claims
1. A calcium alginate gel for internal curing of cement-based materials, characterized in that, It is prepared by a method including the following steps: 1) Under stirring, sodium alginate powder is added to hydrochloric acid with a pH value ≤ 0.01 to obtain an acidified system; 2) Add calcium chloride powder to the acidification system and add water to obtain a mixture; 3) Adjust the pH of the mixture to 6.5-7.5, react for 18-30 hours, and obtain the reaction product; 4) Wash the reaction product and dry it to constant weight to obtain the final product.
2. The calcium alginate gel for internal curing of cement-based materials according to claim 1, characterized in that, In step 1), add 30-80 mL of hydrochloric acid to every 30-70 g of sodium alginate powder.
3. The calcium alginate gel for internal curing of cement-based materials according to claim 1, characterized in that, In step 1), the molar ratio of mannuronic acid and guluronic acid in the sodium alginate powder is 1.5-2.0:
1.
4. The calcium alginate gel for internal curing of cement-based materials according to claim 1, characterized in that, In step 1), the particle size of the sodium alginate powder is less than 200 μm.
5. The calcium alginate gel for internal curing of cement-based materials according to claim 1, characterized in that, In step 2), the amount of calcium chloride powder added satisfies the mass ratio of calcium chloride powder to sodium alginate of 20-100:50; the amount of water added satisfies the concentration of calcium chloride in the resulting mixture of 0.1-1.0 mol / L.
6. The calcium alginate gel for internal curing of cement-based materials according to claim 1, characterized in that, In step 3), sodium hydroxide is used to adjust the pH of the mixture.
7. The calcium alginate gel for internal curing of cement-based materials according to claim 1, characterized in that, In step 4), the drying temperature is 30-50℃.
8. The application of calcium alginate gel as described in claim 1 as an internal curing agent in cement-based materials.
9. The application according to claim 8, characterized in that, The calcium alginate gel is incorporated into the cement-based material at a mass ratio of 0.1% to 2% of the cement mass.
10. The application according to claim 8, characterized in that, The water-cement ratio of the cement-based material is 0.30-0.50.
Citation Information
Patent Citations
A concrete rust-preventing type internal curing agent, a preparation method and application thereof
CN117645425B